Polyetheretherketone (PEEK) cages for anterior column reconstruction in pyogenic vertebral osteomyelitis. (15th April 2019) - Novak, Igor; Košak, Robert; Travnik, Ludvik; Gorenšek, Matevž; Bošnjak, Klemen; Vengust, Rok; Zupanc, Oskar
The objective of study was to evaluate a case series of patients in whom polyetheretherketone (PEEK) cages were used for anterior column reconstruction in vertebral osteomyelitis. Fifteen patients underwent clinical and radiological evaluation with average follow-up of 26 months. Parameters assessed were time of surgery, blood loss, segmental kyphosis or lordosis angle, time to solid bony fusion, ambulatory status, and functional outcome. Mean time of surgery was 150 min with mean blood loss of 530 ml. One patient died in early postoperative period. All patients without preoperative neurologic deficit were walking unaided first day postoperatively. Solid bony fusion was demonstrated in 14 patients, on average 7.1 months postoperatively. Functional outcome at the latest follow-up was excellent, good, or fair in 86%. Two failures with recurrent infection were treated with PEEK cage removal and reinstrumentation. High success rate could be expected when PEEK cages are used for anterior column support in pyogenic vertebral osteomyelitis.